2012
DOI: 10.7314/apjcp.2012.13.12.5995
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Education on Knowledge, Attitude and Behavioral Intention in Family Relative with Colorectal Cancer Patients Based on Theory of Planned Behavior

Abstract: Background: Colorectal cancer is one of most common cancers in women and men and one of the major causes of death due to neoplasia. Colonoscopy is considered as the most accurate diagnostic procedure to detect colorectal cancer at the earlier stages. Objectives: The current study aimed to evaluate the effects of an education program using the Theory of Planned Behavior on promoting behavioral intention among first degree relatives of colorectal cancer patients. Materials and Methods: A quasi-experimental study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 21 publications
2
11
1
Order By: Relevance
“…In the present research, protection motivation showed to be positively correlated with perceived severity and rewards. These findings were consistent with a body of research by Afshari et al, (2016), Baghianimoghadam et al, (2012) and Sadeghi et al, (2019). Yet, these findings were inconsistent with the results reported by Morovati Sharifabad et al, (2009).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present research, protection motivation showed to be positively correlated with perceived severity and rewards. These findings were consistent with a body of research by Afshari et al, (2016), Baghianimoghadam et al, (2012) and Sadeghi et al, (2019). Yet, these findings were inconsistent with the results reported by Morovati Sharifabad et al, (2009).…”
Section: Discussionsupporting
confidence: 93%
“…To explain this correlation, it can be acknowledged that the more trust people put in their own capabilities of adopting protective behaviors, the better their perceived severity of the disease and the higher the chances of adaptive behaviors. These findings were consistent with those of several studies (Baghianimoghadam et al, 2012, Moradhaseli et al, 2019, Searle et al, 2000. In other words, sailors who perceived themselves self-efficacious in adopting protective behaviors, tended to show these behaviors more.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…indicated that education based on the theory of planned behavior (TPB) can increase the individual's behavioral intention to participate in the CRC screening programs and the use of this theory is recommended in the educational interventions which are conducted to increase the behavioral intention to participate in the CRC screening programs. [ 18 ] Regarding what mentioned above, the present study aims to “investigate the effect of educational intervention based on the TPB on the improvement of CRC screening intention among average-risk individuals referring to Asadabad city clinics,” to be a basis and guideline to implement the educational interventions among people at risk of CRC to increase their participation in the screening programs.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most effective theories of health education in the "fertility intentions" is the Theory of Planned Behavior (TPB) [9]. According to this theory, the most important determinant of a person's behavior is "behavioral intention"; then a combination of attitudes toward "behavior", "abstract norms", and "perceived behavioral control" can lead to a behavior:…”
Section: Introductionmentioning
confidence: 99%